E-Module Based on Tri Kaya Parisudha Effectively Improves Science Learning Outcomes - Wahyuni, Luh Tu Selpi; Arnyana, Ida Bagus Putu (MIMBAR PGSD Undiksha, 2022)
Thematic book on science learning in elementary schools is still printed, so learning activities have not been optimal in facilitating various learning styles and have not yet integrated characters based on Balinese local wisdom Tri Kaya Parisudha. Therefore, this study aims to produce an e-module to determine its validity, practicality, and effectiveness. The research subjects are media, material, and language experts. The test subjects were 35 students. Questionnaire data collection methods and practicality and learning outcomes test for effectiveness. The data collection instrument in the questionnaire consists of; media instruments, materials, linguists, and learning outcomes instruments in the form of multiple-choice tests—analysis of quantitative and qualitative descriptive data. The results of this study are; E-Module Based on Tri Kaya Parisudha in Science Learning with the theme of My Friend's Environment for 5th Grade Elementary School Students through the ADDIE Model. E-Modul validity results; material 5.00 is very good; media 5.00 is very good; language 5.00 is very good. 100% practicality is very practical, and the effective test results are based on one sample t-test with the results of t-count 13.45 > t-table 2.03, meaning that t-count is greater than t-table and based on a smaller significance, namely 0.00 < 0.05, meaning that there is an increase in the average science learning outcomes of elementary school students using e-modules based on Tri Kaya Parisudha in the environmental theme of my friend's science learning.